Water User Association Development in China : Participatory Management Practice under Bank-Supported Projects and Beyond - Lin, Zong-cheng (World Bank, Washington, DC, 2012)
Irrigation is crucial to China's agricultural productivity. This report reviews the history of water irrigation in China. It examines the first Bank supported water project to propose both physical rehabilitation and management reform. Local and international experience has shown that participatory irrigation management by farmers (PIM) contribute to institutional improvement. The report looks at self-financing irrigation and drainage districts, or SIDDs which have two main parts: a water-supply corporation (WSC) and water user associations (WUA).